The Symbolism of the Elements of Nature in Poetry "Samih Al-Qasim": Symbolic study - Qaderi, Qader (Al-Adab Journal, 2021)
Symbols have prominent role in field of imagery, and this feature made poets interested. The symbol sometimes appears in the form of words; while are used out of their true meaning. Giving symbolic aspects to natural elements is an art that creates creative implications. Samih Qasim "used symbol and created ideas with secrets in fields of ritual and historical contexts. He is a symbolist poet of contemporary Arab literature, addressing Palestine and suffering of Palestinian, expressing their pains and hopes in language of "symbols" and being a companion of their sorrows and dislocations. By using descriptive-analytical study aims to investigate the symbolism of the elements in the poetry while the poet uses the technique of using natural symbols to express the atrocities committed by Zionists against Palestinian. He has a new orientation in drafting natural symbol which allowed him choosing some natural symbols while he stands with Palestinians and gives part of his personality to mix it with these symbols, extracting different images from their past. Symbolling in his poet includes purposes, such as influencing recipient, provoking feelings, and creating common conscience towards discussion mentioned in poetic text.